Core competencies for the global workplace: A cross-cultural and skill-based simulation project in accounting. (4th July 2021) - Aldamen, Husam; Alkhateeb, Hadeel; Kercher, Kim; Duncan, Keith; Hollindale, Janice
ABSTRACT: This paper examines a multi-faceted workplace simulation project as a curriculum design strategy to address the expanding core competencies that constrained accounting programmes must incorporate. The problem-based learning simulation incorporates technical content with communication and cross-cultural skills competencies. Using Q methodology, this study reveals how students perceived their engagement in the simulation project. The results indicate strong agreement amongst students regarding the effectiveness of the simulation project procedures and the usefulness of its outcomes. However, a clear disparity was evident in terms of students' perspectives on the level of acquiring the cross-cultural and team competencies that the simulation project sought to instil. Suggestions for future implementations are explored.